1999
DOI: 10.1063/1.124897
|View full text |Cite
|
Sign up to set email alerts
|

Er doped nanocrystalline ZnO planar waveguide structures for 1.55 μm amplifier applications

Abstract: Amplifying planar waveguide structures in Er-doped nanocrystalline II/VI semiconductor layer systems were developed by photolithography and wet chemical etching. 2 μm thick planar waveguides on glass substrates with lateral dimensions down to 5 μm with rectangular cross section were realized. By optical excitation a maximum gain of 82 cm−1 could be determined, which is sufficiently high to allow the design of compact planar amplifiers in this material system. The influence of a thermal sintering step on the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 11 publications
0
34
0
2
Order By: Relevance
“…Since it was experimentally observed that the rare earth luminescence efficiency at room temperature increases with the band gap of the semiconductor [2], wide band gap materials such as GaN are especially promising for possible applications. Rare earth luminescence from Nd, Sm, Eu, Tb, Dy, Ho, Er and Tm has also been reported in the hexagonal II-VI semiconductor ZnO [3][4][5][6][7][8][9][10][11][12]. Interest in zinc oxide has recently increased due to the fact that its structural and semiconducting properties are similar to hexagonal GaN, but that, in comparison to GaN, highquality single crystals of ZnO are easier to grow [13].…”
Section: Cern-ep Ch-1211 Geneva 23 Switzerlandmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it was experimentally observed that the rare earth luminescence efficiency at room temperature increases with the band gap of the semiconductor [2], wide band gap materials such as GaN are especially promising for possible applications. Rare earth luminescence from Nd, Sm, Eu, Tb, Dy, Ho, Er and Tm has also been reported in the hexagonal II-VI semiconductor ZnO [3][4][5][6][7][8][9][10][11][12]. Interest in zinc oxide has recently increased due to the fact that its structural and semiconducting properties are similar to hexagonal GaN, but that, in comparison to GaN, highquality single crystals of ZnO are easier to grow [13].…”
Section: Cern-ep Ch-1211 Geneva 23 Switzerlandmentioning
confidence: 99%
“…Several methods for producing RE-doped ZnO have been described in the literature, including sintering [3][4][5], wet-chemical synthesis [6,11], laser ablation [7-10] and co-deposition following evaporation [12]. However, all these methods result in polycrystalline samples, and there exists evidence that the rare earths accumulate at the grain boundaries of polycrystalline ZnO [4].…”
mentioning
confidence: 99%
“…Rare earth doping of ZnO during growth has already been described previously in the literature [3][4][5][6][7][8][9][10]. However, the production of doped layers by ion implantation, the main doping technique used in semiconductor technology, has not been exploited to a great extent.…”
Section: Introductionmentioning
confidence: 99%
“…Until know, different synthesis routes have been developed and reported for preparation Ce-doped ZnO such as pulsed laser deposition, hydrothermal method, thermal evaporation, pyrolysis wet-chemical etching, chemicalcombution process, electrochemical synthesis and sol-gel method [15][16][17][18][19][20][21][22][23]. In this paper, we report a systematic study on the effect of Ce ion as a dopant in ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%